PENERAPAN EVIDENCE BASED NURSING PRENATAL YOGA UNTUK MENGURANGI NYERI PUNGGUNG BAWAH PADA IBU HAMIL TRIMESTER III - Lutfi Riskyta Istikomah (2023)
Pregnancy is a process of fertilization between sperm and egg cells until the formation of a fetus in the uterus until it reaches the birth process. One of the changes in the third trimester of pregnancy is lower back pain. About 60-80% of pregnant women experience low back pain. The reason is because the body's center of gravity shifts forward due to developments in the fetus, causing lower back pain. One of the non-pharmacological therapies to treat low back pain is prenatal yoga. The prenatal yoga movement is able to stimulate the release of endorphins which can relax the back muscles and strengthen the pelvic floor so as to reduce lower back pain. Objective: To determine the effect of prenatal yoga on the intensity of low back pain in third trimester pregnant women. The method is carried out by giving prenatal yoga 6 times with a duration of 30 minutes. The instrument used as a pain measurement tool is using a Numeric Rating Scale. Results: there was a decrease in the intensity of lower back pain felt by pregnant women in the third trimester after prenatal yoga was performed from a moderate to mild pain scale.